Beyond virtue and vice : rethinking human rights and criminal law - Miller, Alice M.; Roseman, Mindy Jane (Pennsylvania studies in human rights., 2019)
Beyond Virtue and Vice examines human rights practices that bring crimninal law to bear on sexuality, gender, and reproduction and seek to articulate if, when, and under what conditions, recourse to criminal law is compatible with human rights in matters of gender expression and equality, sexuality, and reproductive health and justice.